The sequence space BV? (M, p, q, s) on seminormed spaces - Altinok, Hifsi; Altin, Yavuz; Isik, Mahmut (Springer India, 2008)
In this paper we define the sequence space BV sigma(M,p,q,s) on a seminormed complex linear space, by using an Orlicz function. We give various properties and some inclusion relations on this space.
Keywords: Orlicz function; invariant mean; seminorm